Design and construction of laboratory gas pipelines : a practical reference for engineers and professionals - Moody, James, 1950- (Oakville, ON ; New Jersey : Apple Academic Press, 2019)
"This new volume, Design and Construction of Laboratory Gas Pipelines: A Practical Reference for Engineers and Professionals, focuses on design and installation of laboratory gas pipelines. It instructs design engineers, laboratory managers, and installation technicians on how to source the information and specifications they require for the design and installation of laboratory gas systems suitable for their intended use. The current use of specifications predominantly taken from medical gas standards for this type of work is not always suitable; these standards are for use with medical grade gases that have a purity level of 99.5%. The purity levels required in laboratories, however, start at 99.9% for general industrial use through to 99.9995% (Ultra High Purity (UHP)) and higher. Regular medical gas standards are also unsuitable for use with the oxidizing, flammable, and, in some instances, toxic gases that are regularly encountered in laboratories. As need for gas purity increases, the methodology used to design a piping system must vary to meet those parameters, and this reference provides the necessary information and resources"--
Laboratory Gases, Types, and Equipment Encountered -- Laboratory Gas Supply: Plant and Equipment -- Laboratory Gas Pipeline Construction -- Laboratory Gas Pipeline Design -- Gas Data: Inert Gases -- Gas Data: Flammable and Toxic Gases -- Sample Specification.
OCLC-licensed vendor bibliographic record.
Keywords: Gas-fitting.; Gas pipelines -- Design and construction; Laboratories -- Furniture, equipment, etc; HOUSE & HOME / Do-It-Yourself / Plumbing; SCIENCE / General; SCIENCE / Mechanics / Dynamics / Fluid Dynamics